2015
DOI: 10.1016/j.cobeha.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Brain estrogen production and the encoding of recent experience

Abstract: The vertebrate central nervous system integrates cognition and behavior, and it also acts as both a source and target for steroid hormones like estrogens. Recent exploration of brain estrogen production in the context of learning and memory has revealed several common themes. First, across vertebrates, the enzyme that synthesizes estrogens is expressed in brain regions that are characterized by elevated neural plasticity and is also integral to the acquisition, consolidation, and retrieval of recent experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…Because AI use should further deplete any E2 synthesis in OVX females and GDX males, peripheral E2 levels were analyzed at the end of the treatment phase. Some studies have also reported increased T following AI use (Taylor et al, 2017), and so T levels were also assessed. Cortisol was also measured as a negative control, as there is little evidence that AIs should influence cortisol synthesis (Bajetta et al, 1999;Rossi et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because AI use should further deplete any E2 synthesis in OVX females and GDX males, peripheral E2 levels were analyzed at the end of the treatment phase. Some studies have also reported increased T following AI use (Taylor et al, 2017), and so T levels were also assessed. Cortisol was also measured as a negative control, as there is little evidence that AIs should influence cortisol synthesis (Bajetta et al, 1999;Rossi et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have also reported increased T following AI use (Taylor et al, 2017), and so T levels were also assessed. Cortisol was also measured as a negative control, as there is little evidence that AIs should influence cortisol synthesis (Bajetta et al, 1999;Rossi et al, 2009). A few minutes before lights on (i.e., 8:30 A.M.), marmosets entered a stainless-steel transport box (34.1 ϫ 20.65 ϫ 30.8 cm) attached to their home cage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oestrogens were found to play a role in neuronal plasticity and spine synapse formation . Furthermore, many studies have shown positive effects of oestrogens on cognition . In Alzheimer's disease, oestrogens have been shown to protect neurones against the toxicity of amyloid plaques .…”
Section: Sex Steroid Hormones and Brain Functionmentioning
confidence: 99%
“…25,26 Furthermore, many studies have shown positive effects of oestrogens on cognition. [27][28][29] In Alzheimer's disease, oestrogens have been shown to protect neurones against the toxicity of amyloid plaques. 30 Nevertheless, more studies are necessary 31 because investigators from the Women's Health Initiative Memory Study found that therapy with a combination of oestrogen and progestin increased the risk for dementia in postmenopausal women and did not improve their performance in mild cognitive tasks.…”
Section: Sex Steroid Hormones and Brain Functionmentioning
confidence: 99%